Development of E-Leaflet Based Learning Media to Improve Student Learning Outcomes in Excretion System Materials - Diana Puspitasari; Susi Sutjihati; Eka Suhardi (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2023)
The excretory system is material that is considered relatively difficult by students, because teachers experience limitations in using learning media. Therefore, learning media are needed to attract students' attention such as E-Leaflets. This study aims to develop media-based learning E-Leaflet on excretory system material in improving student learning outcomes. This study uses research methods Research and Development using the ADDIE model. The subject of this study were 34 students. Limited trials in this study using the design one group pretest-postest. The instruments used in this study consisted of expert validation sheets, multiple choice instruments and student response questionnaires E-Leaflet. The multiple choice instrument is used to measure all levels of learning objectives. While the student questionnaire sheet is used to determine student responses to learning media. The expert validation instrument is used to find out. The results of the study show that media validationE-Leaflet expert included in the valid category without revision. While the validation of material content experts gets valid and appropriate category for use in the learning process. The results of the student response questionnaire received a positive response . The results of the N-Gain analysis show that the criteria are moderate. This shows that learning media E-Leaflet can improve students' biology learning outcomes.